2014
DOI: 10.1038/nprot.2014.116
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron-based small-angle X-ray scattering of proteins in solution

Abstract: Summary With recent advances in data analysis algorithms, X-ray detectors, and synchrotron sources, small-angle X-ray scattering (SAXS) has become much more accessible to the structural biology community than ever before. Although limited to ~10 Å resolution, SAXS can provide a wealth of structural information on biomolecules in solution and is compatible with a wide range of experimental conditions. SAXS is thus an attractive alternative when crystallography is not possible. Moreover, advanced usage of SAXS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
168
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 47 publications
1
168
0
2
Order By: Relevance
“…Scattering patterns I(q) are also shown as Kratky plots (q 2 I(q) vs q, Figure S2A) indicating that all proteins are properly folded in solution. Typically, a globular, structured protein exhibits a pronounced maximum (bell-shaped curve), whereas a random chain (for example, an unfolded protein) will plateau (47,48). Then, Porod-Debye plots (q 4 I(q) vs. q 4 ) were generated and confirmed the compactness of all proteins ( Figure S2B and Table S2).…”
Section: Saxs Data Analysismentioning
confidence: 81%
“…Scattering patterns I(q) are also shown as Kratky plots (q 2 I(q) vs q, Figure S2A) indicating that all proteins are properly folded in solution. Typically, a globular, structured protein exhibits a pronounced maximum (bell-shaped curve), whereas a random chain (for example, an unfolded protein) will plateau (47,48). Then, Porod-Debye plots (q 4 I(q) vs. q 4 ) were generated and confirmed the compactness of all proteins ( Figure S2B and Table S2).…”
Section: Saxs Data Analysismentioning
confidence: 81%
“…It was found that even at low dose (< 0.5 Gy) chromatin shows radiation damage as evidence by a change in hydrodynamic size that was likely due to single-strand breaks in DNA [58]. In SAXS, radiation damage most often present itself as aggregation [59]. Even with sample flow enable, radiation damage in lysozyme, evidenced by an increase in radius of gyration ( R g ), still occurs as early as 250 ms exposure time [11].…”
Section: Discussionmentioning
confidence: 99%
“…A number of proteins have been used as calibration standards, the four main ones being: i) lysozyme [6], ii) bovine (BSA) [6,8] or human serum albumin (HSA) [9] and iii) glucose isomerase [5]. For proteins to be considered as a calibration standard they need a number of attributes, specifically being; i) cheap and abundantly available, ii) monodisperse and iii) thermodynamically stable over time, so giving reproducible and expected results, most commonly using Guinier analysis to determine results such as radius of gyration (Rg) and intensity at zero angle I(0) [4,10].…”
Section: Introductionmentioning
confidence: 99%